Moscow Place Names in “Master and Margarita” by M. A. Bulgakov. Patriarshiye Ponds: History and Literature - Y. Shi (Научный диалог, 2018)
The study is devoted to the functioning of place names in the artistic space of the novel “Master and Margarita” by M. A. Bulgakov. The author assumes that place names are the evidences of historical conditions of development of society, they reflect historical and cultural information. It is noted that place names keep information about people’s activities in different eras, about the migration of peoples, about historical events and personalities, about the mythological views of the people. It is argued that the historical and linguistic analysis of place names, which occupy a significant place in the fabric of a work of art, should be based on the determining the relations of nominations with history and culture of a country and a city. The author shows that the study of historical component of the material of the novel “Master and Margarita” allows deeper understanding of the author’s idea, his idea of contrasting light and darkness, reflected in the names of urban areas and streets. Special attention is paid to the name Patriarshiye Ponds , including related historical data. The controversial issues of reliability of certain aspects of the novel are highlighted. The conclusion about the importance of a comprehensive study of toponymic units in Bulgakov’s works is made.